Correlations of spectral accelerations in the Chilean subduction zone - CANDIA AGUSTI, GABRIEL ALFONSO; Alan Poulos; Juan Carlos de la Llera; Jorge G.F. Crempien; Jorge Macedo (My University, 2020)
The correlation between spectral accelerations is key in the construction of conditional mean spectra, the computation of vector-valued seismic hazard, and the assessment of seismic risk of spatially distributed systems, among other applications. Spectral correlations are highly dependent on the earthquake database used, and thus, region-specific correlation models have been developed mainly for earthquakes in western United States, Europe, Middle East, and Japan. Correlation models based on global data sets for crustal and subduction zones have also become available, but there is no consensus about their applicability on a specific region. This study proposes a new correlation model for 5% damped spectral accelerations and peak ground velocity in the Chilean subduction zone. The correlations obtained were generally higher than those observed from shallow crustal earthquakes and subduction zones such as Japan and Taiwan. The study provides two illustrative applications of the correlation model: (1) computation of conditional spectra for a firm soil site located in Santiago, Chile and (2) computation of bivariate hazard for spectral accelerations at two structural periods.
Keywords: earthquake scenarios; ground motion correlations; subduction zone earthquakes; chile; europe; japan; middle east; taiwan; united states; distributed database systems; earthquakes; hazards; risk assessment; conditional mean spectrum; correlation modeling; crustal earthquakes; peak ground velocity; spatially-distributed system; spectral acceleration; spectral correlation; western united states; correlation; damping; ground motion; hazard assessment; peak acceleration; risk assessment; spectral analysis; subduction zone; distributed computer systems